Fine-Tuned Phi-3-Mini and Mistral-7B Hallucination Rates in Long-Context RAG Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 16 peer-reviewed papers addressing the following research question: How do fine-tuned versions of Phi-3-mini and Mistral-7B on religious domain data compare in hallucination rates versus their base versions on long-context RAG benchmarks. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.7/10. This report is a machine-generated litera
Machine-generated literature synthesis.